KITAB'UN FI ZIKRI'L DAVAL'I VE ASNAFI'L KUFR'I ADLI ESERIN TAHKIK, KARŞILAŞTIRMA VE ELEŞTIRISI - AL-BAJALAN, SALAM AZEEZ ALİ (Fırat Üniveristesi, 2019)
Hz. Peygamberin vefatı sonrası ortaya çıkan sorunlara rağmen, ümmet hala dinine ve inançlarına bağlıydı. Taki Havaric fırkası doğup ve Hz. Ali'yi tahkime zorladılar ve tekfir ettiler. O günden sonra farklı fırkalar peydah olup aralarında ise anlaşmazlık daha da çoğalmıştır. Her biri gittikçe dürüst inançtan uzaklaşıp; bidat, heves ve parçalanmaya yönelmiştir. Daha sonra ortaya çıkmış olan ve Resulullah (A.S.V) tarafından sıfat ve sayılarından haberdar olduğumuz fırkalar ve el yazma nüsha sahibininde ortaya koyduğu isim, taraftar, başlangıç, temel gurup ile dalları ve inançları asıl konumuzdur. Nüsha sahibi kanıt ve delillerini araştırıp, Kur'an-i Kerim ve Peygamber efendimizin sözlerine dayanarak onları cevaplıyor. Fırka-tul Naciye (kurtulmuş firka) usul ve metodlarını beyan ediyor. Ayrıca el yazılı nüshanın, konu alanındaki diğer kitaplarla müvazesini ve farklılığını göstermek maksadıyla, kıyası yapılmıştır. Bu görüşleri Kuran ve hadise göre değerlendirdikten sonra, doğru bulduklarımızı burada zikrettik. Buna ek olarak selefin bazı olumsuz ictahatlarına, herhangi bir konudaki hatalarını veya taklit yoluyla düştükleri hatalardan ötürü onlar, yargılamaktan kaçındık.

After the death of the Prophet, peace be upon him and his family, the Ummah remained keeping its religion and faith until the appearance of the group Khwarij, which contested Imam Ali during the arbitration and accused him of infidelity (Al-Kufr). Later, the groups multiplied and disagreed among themselves, and became various groups and parties and grew further away from the correct doctrine (Al-Aqeedah) and closer to heresy, whims and separation, which appeared later on, and which the Messenger of Allah, peace and blessings be upon him, and the owner of this manuscript mentioned and reminded us of them and of their number and the emergence of each one of them and the sects of these basic groups and the branches of each one of them, their shortcomings and arguments and respond to those arguments and refute them depending on what is cited in the book of Allah (the Quran) and the Sunnah of His Messenger. Then there is the statement of the surviving group, and its correct doctrine according to the author in his manuscript which we have investigated, as we have compared his book with other books and referred to the terms of agreement as well as the differences. Furthermore, we have preferred what we found correct after being measured by the Book of Allah and the Sunnah of His Messenger. We have emphasized the avoidance of judging the righteous based on some of their incorrect Ijtihads or slips as a result of ignorance of a certain issue, negligence or imitation as long as they worship Allah and do not involve in polytheism, and adhere to the pillars of faith and pillars of Islam tirelessly and without boredom.
A Book about the Stray Groups and types of infidelityStudy, investigation and criticism by
Keywords: Din